2015
DOI: 10.1016/j.micres.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and evaluation of multi-trait plant growth promoting rhizobacteria for their growth promoting and disease suppressing effects on ginger

Abstract: In this study, 100 PGPR strains isolated from different varieties of ginger (Zingiber officinale Rosc.) were first characterized for their morphological, biochemical, and nutrient mobilization traits in vitro. The PGPR were also screened in vitro for inhibition of Pythium myriotylum causing soft rot in ginger. Results revealed that only five PGPR showed >70% suppression of P. myriotylum. These 5 PGPR viz., GRB (Ginger rhizobacteria) 25--Burkholderia cepacia, GRB35--Bacillus amyloliquefaciens; GRB58--Serratia m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(92 citation statements)
references
References 42 publications
5
86
0
1
Order By: Relevance
“…The ability of the bacterial endophytes to suppress the growth of the pathogen maybe reflected to their ability to produced hydrolytic enzyme responsible for the degradation of the pathogen cell wall. The present findings is supported by Dinesh et al, (2015) who reported that isolate Bacillus GRB35 amyloliquefaciens exhibited 78.51% inhibition in growth of P. myriotylum in ginger.…”
Section: Efficacy Of Bacterial Endophytes Against Pythium Sppsupporting
confidence: 88%
“…The ability of the bacterial endophytes to suppress the growth of the pathogen maybe reflected to their ability to produced hydrolytic enzyme responsible for the degradation of the pathogen cell wall. The present findings is supported by Dinesh et al, (2015) who reported that isolate Bacillus GRB35 amyloliquefaciens exhibited 78.51% inhibition in growth of P. myriotylum in ginger.…”
Section: Efficacy Of Bacterial Endophytes Against Pythium Sppsupporting
confidence: 88%
“…Increases in growth and yield of crops in response to inoculation with PGPR have been repeatedly reported (Baris et al, 2014;Dinesh et al, 2015;Imran et al, 2015;Saia et al, 2015). PGPR exert positive effect on plant growth by direct mechanisms, such as biological N2 fixation, phosphate solubilisation and production of growth regulators (phytohormones), or by indirect mechanisms, such as prevention of the deleterious effects of plant pathogens, production of inhibitory substances (siderophore, antibiotics), or increase of natural resistance of the host (Glick, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The plates were incubated at 28 °C for three days. Finally, the population of PGPR was determined as number of CFU g −1 soil …”
Section: Methodsmentioning
confidence: 99%